Effects of light intensity on growth and lipid production in microalgae grown in wastewater - Nzayisenga, Jean Claude; Farge, Xavier; Groll, Sophia Leticia; Sellstedt, Anita (Biotechnology for biofuels, 2020)
Background Cultivation of microalgae in wastewater could significantly contribute to wastewater treatment, biodiesel production, and thus the transition to renewable energy. However, more information on effects of environmental factors, including light intensity, on their growth and composition (particularly fatty acid contents) is required. Therefore, we investigated the biomass and fatty acid production of four microalgal species, isolated in the Northern hemisphere and grown at three light intensities (50, 150 and 300 μE m −2 s −1 ). Results Increases in light intensities resulted in higher biomass of all four species and, importantly, raised fatty acid contents of both Desmodesmus sp. and Scenedesmus obliquus . Fourier-transform IR spectrometry analysis showed that the increases in fatty acid content were associated with reductions in protein, but not carbohydrate, contents. Assessment of fatty acid composition revealed that increasing light intensity led to higher and lower contents of oleic (18:1) and linolenic (18:3) acids, respectively. The microalgae consumed more than 75% of the nitrogen and phosphorus present in the wastewater used as growth medium. Conclusion The results show the importance of optimizing light intensities to improve fatty acid production by microalgae and their quality as sources of biodiesel. In addition, increase in fatty acid content is associated with decrease in protein content.